2008
DOI: 10.1167/iovs.07-1488
|View full text |Cite
|
Sign up to set email alerts
|

Versican and Fibrillin-1 Form a Major Hyaluronan-Binding Complex in the Ciliary Body

Abstract: Fibrillin-1, versican, and hyaluronan form a unique complex in the ciliary nonpigmented epithelium, and two cleavage products of this complex were shown to exist in the vitreous body. This newly clarified fibrillin-versican-hyaluronan (FiVerHy) complex and its cleavage products may be indispensable for the physiological properties important to the ciliary body and vitreous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Hirani et al (2007) have shown that LTBP2 speciWcally binds to the amino-terminal region of Wbrillin-1, but not to Wbrillin-2; the major Wbrillin-1 binding site resides close to the carboxyl-terminus of LTBP2. Since LTBP2 interacts and co-localizes with Wbrillin-1 (Hirani et al 2007;Ohno-Jinno et al 2008), it is not surprising to Wnd microspherophakia in some of the MSF patients (Maumenee 1981). As the carboxyl-terminus from amino acids 1816-1821 is lost in the mutant LTBP2 in patients from family 1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hirani et al (2007) have shown that LTBP2 speciWcally binds to the amino-terminal region of Wbrillin-1, but not to Wbrillin-2; the major Wbrillin-1 binding site resides close to the carboxyl-terminus of LTBP2. Since LTBP2 interacts and co-localizes with Wbrillin-1 (Hirani et al 2007;Ohno-Jinno et al 2008), it is not surprising to Wnd microspherophakia in some of the MSF patients (Maumenee 1981). As the carboxyl-terminus from amino acids 1816-1821 is lost in the mutant LTBP2 in patients from family 1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…b Versican staining is observed from the pars plana to the peripheral retina, but staining toward the posterior pole is weaker than HA staining. c No versican staining is observed at the posterior pole of the retina Int Ophthalmol ciliary body [14], vitreous [15][16][17], trabeculum [18][19][20], and cornea [21]. In particular, an association between versican expression in the ciliary body and HA production has been described.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4 shows the proposed structural model of the elastichydrated matrix in the dermis. Furthermore, the fibrillin-versican-hyaluronan network is also observed in the ciliary body (16). …”
Section: Versican Is a Chondroitin Sulfate Proteoglycan And Is Criticmentioning
confidence: 94%